Potential of mRNA-based vaccines for the control of tick-borne pathogens in one health perspective - González-Cueto, E; de la Fuente, J; López-Camacho, C (Frontiers Media, 2024)
The One Health approach, which integrates the health of humans, animals, plants, and ecosystems at various levels, is crucial for addressing interconnected health threats. This is complemented by the advent of mRNA vaccines, which have revolutionized disease prevention. They offer broad-spectrum effectiveness and can be rapidly customized to target specific pathogens. Their utility extends beyond human medicine, showing potential in veterinary practices to control diseases and reduce the risk of zoonotic transmissions. This review place mRNA vaccines and One Health in the context of tick-borne diseases. The potential of these vaccines to confer cross-species immunity is significant, potentially disrupting zoonotic disease transmission cycles and protecting the health of both humans and animals, while reducing tick populations, infestations and circulation of pathogens. The development and application of mRNA vaccines for tick and tick-borne pathogens represent a comprehensive strategy in global health, fostering a healthier ecosystem for all species in our interconnected world.